2017
DOI: 10.1002/pc.24360
|View full text |Cite
|
Sign up to set email alerts
|

Transcrystalline induced by MWCNTs and organic nucleating agents at the interface of glass fiber/polypropylene

Abstract: The interfacial crystallization at glass fiber/PP interface in the presence of multiwalled cabon nanotubes (MWCNTs) and organic nucleating agents (NAs) along fiber surface was investigated in this study. MWCNTs and NAs formed a uniform coating layer on glass fiber surface via dipping in well‐dispersed MWCNTs and NAs aqueous dispersions. Transcrystalline (TC) structure formed by the strong nucleating ability of MWCNTs/NAs coated glass fiber surface. There existed a detectable difference in TC structure induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…He et al 9 revealed that thickness and weight fraction of MWCNTs on the GF surface could be modulated by controlling the CVD conditions, and the obtained MWCNTs-GF/epoxy composites showed greatly improved electrical conductivity, thermo-mechanical, and flexural properties. Ye et al 10 prepared a uniform coating layer composed of MWCNTs and organic nucleating agents (NAs) on the GF surface via the dipping process and then studied the crystallization of the MWCNTs-GF/Polypropylene interface. It was found that the introduction of MWCNTs and NAs on the GF surface could construct a high-density transcrystalline structure, which helps to enhance the interfacial adhesion of GF/Polypropylene composites.…”
Section: Introductionmentioning
confidence: 99%
“…He et al 9 revealed that thickness and weight fraction of MWCNTs on the GF surface could be modulated by controlling the CVD conditions, and the obtained MWCNTs-GF/epoxy composites showed greatly improved electrical conductivity, thermo-mechanical, and flexural properties. Ye et al 10 prepared a uniform coating layer composed of MWCNTs and organic nucleating agents (NAs) on the GF surface via the dipping process and then studied the crystallization of the MWCNTs-GF/Polypropylene interface. It was found that the introduction of MWCNTs and NAs on the GF surface could construct a high-density transcrystalline structure, which helps to enhance the interfacial adhesion of GF/Polypropylene composites.…”
Section: Introductionmentioning
confidence: 99%
“…The complete TC layer was an important factor for improving interfacial performance and enhancing mechanical properties. 44 And the isothermal crystallization POM images of CF/PP composites without PP-g-MAH were shown in Figure S2, which had almost same results. It was noteworthy that the PEI-CNT-CF/PP (with PP-g-MAH) had denser TC structure.…”
Section: Tc Observation and Dsc Measurement Of Pp/cf Micro-compositesmentioning
confidence: 73%
“…Figure (c,d1) showed the enlarged micrograph of the composite samples of the marked area in red dashed lines. In Figure (c,d), it was observed that the detached GFs surface of the fractured GF/PP composite was pretty smooth, indicating a relatively poor interfacial adhesion between GFs and PP matrix . Noticeably, an obvious enhancement of the interfacial adhesion was observed for GF/β‐PP composite based on the observation that a layer of remnant matrix polymer was adhered on the fractured GFs surface [Figure (d,d)].…”
Section: Resultsmentioning
confidence: 97%